Profile of Genetic Concepts Understanding for 9th Junior High School - Bhian Ananda Javanica Rubiyanto; Puguh Karyanto; Bowo Sugiharto (Postgraduate, University of Mataram, 2022)
This research aims to analyze the understanding of studentsâ€™ concepts in 9th grade junior high school on genetic material. Mastery of concepts is one of the important aims in the process of learning biology. In this research, it is used case study method with the research design pretest only one group design. The number of samples is 50 9th grade students consisting of 35 female students and 15 male students. The average of sample is 14–15 years old. The research instruments consist of 15 multiple choice questions on genetic material. The results show that the understanding of the concept of most of the students is about -0.19 logit. There are differences in mastering the concept of understanding between male and female students at certain concepts. It is used the Rasch model that can explain well the profile of students' conceptual understanding using output table 3.1 summary statistics: reliability person and separation person. Response patterns are known from person fit and scalogram table, as well as output table 30. Item: dif, between/within is applied to detect question bias both genders. The results of profile in understanding the concept of biology learning on genetic concepts require further researches to be able to improve the learning process so as to elevate the understanding of genetic concepts for 9th grade junior high school students